Islamic liberation theology resisting the empire - Dabashi, Hamid 1951- (Routledge, 2008)
Presenting criticism of contemporary politics, this title argues that after 9/11 we have not seen a new phase in a confrontation between Islam and the West, but that such categories have in fact collapsed and exhausted themselves